The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
The 2nd International Electronic Conference on Water Sciences 2017
DOI: 10.3390/ecws-2-04961
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Demand Pattern on Calibration Process

Abstract: Mathematical models are the basic tool that simulates the operation of the Water Distribution System (WDS). Building such a tool is a complex task that requires as much detail as possible. The information needed to build a model can be divided into two categories: network data and WDS operating data. The first group includes pipe and node attributes, such as pipe length, pipe diameter, pipe roughness, junction elevation, and junction demand. The second category includes data specifying network performance such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In the same direction, the authors from [36] analyzed the groundwater resources used for irrigation and identified a non-linear multi-year optimal distribution model of groundwater, which is capitalized for obtaining a sustainable utilization of groundwater in irrigation. The water demand pattern is analyzed in terms of impact over the calibration process in [37]. The authors of [38] presented the optimization of water treatment regarding the water turbidity Processes 2020, 8, 282 3 of 18…”
mentioning
confidence: 99%
“…In the same direction, the authors from [36] analyzed the groundwater resources used for irrigation and identified a non-linear multi-year optimal distribution model of groundwater, which is capitalized for obtaining a sustainable utilization of groundwater in irrigation. The water demand pattern is analyzed in terms of impact over the calibration process in [37]. The authors of [38] presented the optimization of water treatment regarding the water turbidity Processes 2020, 8, 282 3 of 18…”
mentioning
confidence: 99%